Save the catch - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Managing small-scale fisheries. Alternative directions and methods By F Berket, R Mahon, P McConney et al, IDRC, Canada, 2001. 320 pp. ISBN 0 88936 943 7 CAD 35 Euro 25.10